COVID-19 (Symptomatic Non-Respiratory) with Type 2 Diabetes Mellitus - Nursin Abdul Kadir; Ida Parwati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
COVID-19 is a respiratory infection caused by a new strain of Coronavirus, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), which is highly contagious, primarily through respiratory droplets and contact. Typical symptoms include fever, cough, and shortness of breath. Weakness, nausea, and vomiting are often accompanied by respiratory symptoms but are sometimes confusing when these symptoms occur without respiratory symptoms. COVID-19 can affect any age group, are more common in adults and males and increase in patients with comorbidities. One of the most common comorbidities is Diabetes Mellitus (DM). A 40-year-old male patient complained of fever and weakness for three days. Nausea and vomiting since nine days before hospital admission, accompanied by painful swallowing, heartburn, and decreased appetite. History of going out of town and eating with friends 14 days before access to the hospital. 3 3 Laboratory examination results: 6600 leukocytes/mm , 264,000/mm platelets, NLR 2.3, 209 mg/dL of blood glucose, HbA1C 8.6%, SGOT 67 IU/L, SGPT 102 IU/L, IgG SARS-CoV-2 reactive, positive TCM SARS-CoV-2 (N2 Ct 18 and E Ct 20.3), and the duration of negative conversion of RT-PCR SARS-CoV-2 results was 19 days. The SARS-CoV-2 virus not only infects pneumocytes but also gastrointestinal, pancreatic, and endothelial cells via ACE2 receptors in DM patients, causing increased cell wall permeability to foreign pathogens and viral replication in the gastrointestinal lining cells. Subsequent enterocyte invasion causes malabsorption resulting in enteric symptoms. Uncontrolled glycemia conditions can slow viral shedding, so the length of negative conversion of RT-PCR SARS-CoV-2 results is prolonged. Based on the data above, the diagnosis in this patient was COVID-19 (symptomatic non-respiratory) with type 2 DM.